2012
DOI: 10.1258/jrsm.2011.110256
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of non-UK-qualified doctors working within the UK regulatory framework: a qualitative study

Abstract: Objective To explore the experience of non-UK-qualified doctors in working within the regulatory framework of the General Medical Council (GMC) document Good Medical Practice. Design Individual interviews and focus groups. Setting United Kingdom. Participants Non-UK-qualified doctors who had registered with the GMC between 1 April 2006 and 31 March 2008, doctors attending training/induction programmes for non-UK-qualified doctors, and key informants involved in training and support for non-UK-qualified doctors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 21 publications
4
73
0
1
Order By: Relevance
“…There can also be cultural issues including feelings of social isolation and cultural disorientation. [15][16][17][18][19] Interaction adjustment may emerge in subtle ways, such as unfamiliarity with nonverbal communication, 8,20,21 which may also present themselves in work-specific settings. Lack of professional and personal networks can make integration and adaptation into the NHS difficult.…”
Section: Adjustment -Comfort Associated With Various Non-work Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…There can also be cultural issues including feelings of social isolation and cultural disorientation. [15][16][17][18][19] Interaction adjustment may emerge in subtle ways, such as unfamiliarity with nonverbal communication, 8,20,21 which may also present themselves in work-specific settings. Lack of professional and personal networks can make integration and adaptation into the NHS difficult.…”
Section: Adjustment -Comfort Associated With Various Non-work Factorsmentioning
confidence: 99%
“…16 Overseas doctors may have little experience of patients asking questions about treatment options or questioning the doctor's authority. 8,20 There are efforts to help doctors make the transition to new countries. Some deaneries (Deaneries are the bodies responsible for postgraduate medical education at regional level in the UK) already offer specific induction courses targeted at overseas doctors, but the GMC are piloting an induction programme for all doctors new to working in the NHS.…”
Section: Adjustment -Comfort Associated With Various Non-work Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a greater proportion of UK-registered doctors have qualified abroad than had 10 years ago, although the proportion has reduced from a peak of just under 40% in 2005 to 37% in 2011 (GMC 2011(GMC , 2012. Slowther et al (2009Slowther et al ( , 2012 identified that doctors who qualified outside the UK can face difficulties when they start to practise in this country, such as unfamiliarity with UK legal and ethical standards. The UK General Medical Council (GMC) has recognised that overseas-qualified doctors need better support and need to be properly inducted into UK practice (GMC 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The patient-centred approach emphasised in the UK can be at odds with the focus of regulators in many countries (Rand 2009), with doctors' own cultural values and experience (Manderson & Allotey 2003;Hall et al 2004;Jaffrey & Faroqui 2005;Hamilton 2009;Slowther et al 2009;Chen et al 2011;Dahm 2011;Slowther et al 2012) and with patients' expectations of consultations or the physician-patient power dynamic (Dorgan et al 2009;Hamilton 2009). Communicating emotional support for patients can be a challenge for doctors who have graduated overseas (Fiscella et al 1997;Hawken 2005).…”
Section: Introductionmentioning
confidence: 99%